COVID‐19 outcomes in patients waitlisted for kidney transplantation and kidney transplant recipients. Issue 4 (8th November 2020) - Craig‐Schapiro, Rebecca; Salinas, Thalia; Lubetzky, Michelle; Abel, Brittany T.; Sultan, Samuel; Lee, John R.; Kapur, Sandip; Aull, Meredith J.; Dadhania, Darshana M.
Abstract : The COVID‐19 pandemic has brought unprecedented challenges to the transplant community. The reduction in transplantation volume during this time is partly due to concerns over potentially increased susceptibility and worsened outcomes of COVID‐19 in immunosuppressed recipients. The consequences of COVID‐19 on patients waitlisted for kidney transplantation, however, have not previously been characterized. We studied 56 waitlisted patients and 80 kidney transplant recipients diagnosed with COVID‐19 between March 13 and May 20, 2020. Despite similar demographics and burden of comorbidities between waitlisted and transplant patients, waitlisted patients were more likely to require hospitalization (82% vs. 65%, P = .03) and were at a higher risk of mortality (34% vs. 16%, P = .02). Intubation was required in one third of hospitalized patients in each group, and portended a very poor prognosis. The vast majority of patients who died were male (84% waitlist, 100% transplant). Multivariate analysis demonstrated waitlist status, age, and male sex were independently associated with mortality. COVID‐19 has had a dramatic impact on waitlisted patients, decreasing their opportunities for transplantation and posing significant mortality risk. Understanding the impact of COVID‐19 on waitlist patients in comparison to transplant recipients may aid centers in weighing the risks and benefits of transplantation in the setting of ongoing COVID‐19. Abstract : Comparisons of kidney waitlisted patients and transplant recipients show that waitlisted patients are more likely to require hospitalization and are at higher mortality risk, which is independently associated with waitlist status, age, male sex, and diabetes.